Analisis Framing Kontroversi Pada Olimpiade Paris 2024 di CNN Indonesia dan Republika - Akbar, Fazriel Irviana; Nanda, Ertika (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
The 2024 Paris Olympics has had controversies such as a boxer suspected of being transgender taking part in the Olympics and rules prohibiting the use of the hijab for French athletes. The aim of this research is to analyze the framing of controversy at the 2024 Paris Olympics in the online media CNN Indonesia and Republika. This research uses a qualitative analysis method with Robert N Entman's framing analysis which consists of problem definition, source of the problem, moral decisions taken, and problem resolution. This research uses articles released from 18 July to 1 August 2024 on CNN Indonesia and Republika. The results of this research explain that the difference between CNN Indonesia and Republika is that CNN Indonesia tends to be neutral and provides justification for decisions taken by related parties. Meanwhile, Republika emphasized criticism and highlighted aspects of discrimination in these two issues. The difference in reporting on the controversial issue of female boxers is that CNN Indonesia is more inclined to support these athletes and the role of athletes by emphasizing personal rights that free athletes to take part in any competition, whereas in Republika they are more likely to discuss criticizing policies taken by certain authorities. On the issue of banning the use of the hijab by French Muslim female athletes, CNN Indonesia emphasized the word proselytism which France wanted to prevent and explained that the rule forbidding the use of the hijab only applies to France, while Republika explained that this rule exists because of Islamophobia and racism, thus demanding that the IOC this rule can be omitted.